1978
DOI: 10.1128/jb.134.2.440-445.1978
|View full text |Cite
|
Sign up to set email alerts
|

Early-blocked asporogenous mutants of Bacillus subtilis are lysogenized at reduced frequency by temperate bacteriophages

Abstract: The establishment of lysogeny in early-blocked asporogenous (Spo-) mutants of Bacillus subtilis 168, which were also defective in the production of antibiotics

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

1979
1979
1987
1987

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…spoOA mutations are pleiotropic for many properties associated with sporulation, such as the ability to be transformed with exogenous DNA, the sensitivity to bacteriophage 42 and 415, and the production of antibiotics (5,12,20,22). We reported recently another phenotypic character of spoOA and spoOB mutants; that is, the frequency of lysogenization by temperate bacteriophages is reduced to 10 to 20% that of wild-type strain 168 (9).…”
mentioning
confidence: 95%
“…spoOA mutations are pleiotropic for many properties associated with sporulation, such as the ability to be transformed with exogenous DNA, the sensitivity to bacteriophage 42 and 415, and the production of antibiotics (5,12,20,22). We reported recently another phenotypic character of spoOA and spoOB mutants; that is, the frequency of lysogenization by temperate bacteriophages is reduced to 10 to 20% that of wild-type strain 168 (9).…”
mentioning
confidence: 95%
“…These results suggest that an excess amount of the spoOA gene product inhibits the vegetative growth of B. subtilis, whereas an adequate amount of the active spoOA product at the wild-type level is essential for sporulation. A number of workers have reported that spoOA mutants have several properties different from those of the wild-type strain even in the vegetative-growth phase (2,5,16,18,25). Further studies are necessary to elucidate the expression and function of the spoOA gene in switching the cells from the vegetative state to begin sporulation.…”
Section: Discussionmentioning
confidence: 99%
“…Production of antibiotics. The ability to produce antibiotics was determined as described previously (16), except that the spoOA mutant 1S9 or SR22 was used as an indicator strain.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations